Hydrocortisone, Ascorbic Acid, and Thiamine (HAT) Therapy Decreases Oxidative Stress, Improves Cardiovascular Function, and Improves Survival in Murine Sepsis. Issue 4 (April 2020) - Kim, John; Arnaout, Leen; Remick, Daniel
ABSTRACT: Introduction: A small clinical trial showed HAT therapy improved survival but no studies have been reported in animal models to examine potential mechanisms. Methods: Sepsis was induced in female mice using the cecal ligation and puncture (CLP) model. Physiologic parameters including heart rate (HR), pulse distension (PD), and respiratory rate (RR) were measured noninvasively at baseline, 6 and 24 h post CLP. These measurements stratified mice into predicted to live (Live-P) or die (Die-P). Mice were randomized to receive HAT therapy or vehicle. Oxidative stress was measured in peritoneal exudative cells 24 h after CLP. Results: HR, PD, and RR all declined within the first 6 h of sepsis and were significantly lower in the Die-P mice compared with Live-P. HR 6 h post-CLP best predicted mortality and continued to decline between 6 and 24 h post CLP. Oxidative stress in peritoneal cells harvested 24 h post CLP (determined by 8 isoprostaglandin F2α and protein carbonyl derivatives) was significantly higher in the Die-P mice. HAT therapy was initiated 7 h post-CLP after mortality prediction and stratification. HAT significantly reduced oxidative stress in the Die-P mice without altering these parameters in the Live-P mice. HAT treatment prevented the decline in HR, again only in the Die-P mice. Mice treated with HAT therapy had significantly better survival. Conclusions: Physiologic parameters accurately predicted mortality. Die-P mice had significant oxidative stress compared with Live-P. HAT therapy significantly decreased oxidative stress, increased HR, and improved survival in the Die-P mice. These data suggest that HAT exerts a beneficial effect through reducing oxidative stress and improving cardiovascular function. Abstract : Supplemental Digital Content is available in the text